2004
DOI: 10.1016/j.jacc.2004.05.065
|View full text |Cite
|
Sign up to set email alerts
|

Impact of physical deconditioning on ventricular tachyarrhythmias in trained athletes

Abstract: Frequent and/or complex ventricular tachyarrhythmias in trained athletes (with and without cardiovascular abnormalities) are sensitive to brief periods of deconditioning. In athletes with heart disease, the resolution of such arrhythmias with detraining may represent a mechanism by which risk for sudden death is reduced. Conversely, in athletes without cardiovascular abnormalities, reduction in frequency of ventricular tachyarrhythmias and the absence of cardiac events in the follow-up support the benign clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(74 citation statements)
references
References 25 publications
2
71
1
Order By: Relevance
“…Among them, 71 athletes (corresponding to 0.4% of all screened athletes) exhibited >2000 PVBs or nonsustained VT. In this study, most athletes with VAs had no evidence of underlying structural abnormalities, the arrhythmias tended to decrease after detraining, and the follow‐up was uneventful: all these findings are consistent with the concept that VAs may be considered a feature of the “athlete's heart.”4, 5 Moreover, Palatini et al compared 40 endurance athletes with 40 sedentary individuals and found that the prevalence of complex VAs at ambulatory electrocardiographic monitoring was higher in trained individuals 10. Other studies comparing the prevalence of VA at 24‐hour ambulatory electrocardiographic monitoring in healthy athletes versus sedentary individuals disproved the concept of a proarrhythmic effect of sports activity by demonstrating that only a minority of athletes exhibited frequent or complex VAs with a prevalence that did not differ with that of their sedentary counterpart6, 7, 8, 9, 11 (Table S4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 71 athletes (corresponding to 0.4% of all screened athletes) exhibited >2000 PVBs or nonsustained VT. In this study, most athletes with VAs had no evidence of underlying structural abnormalities, the arrhythmias tended to decrease after detraining, and the follow‐up was uneventful: all these findings are consistent with the concept that VAs may be considered a feature of the “athlete's heart.”4, 5 Moreover, Palatini et al compared 40 endurance athletes with 40 sedentary individuals and found that the prevalence of complex VAs at ambulatory electrocardiographic monitoring was higher in trained individuals 10. Other studies comparing the prevalence of VA at 24‐hour ambulatory electrocardiographic monitoring in healthy athletes versus sedentary individuals disproved the concept of a proarrhythmic effect of sports activity by demonstrating that only a minority of athletes exhibited frequent or complex VAs with a prevalence that did not differ with that of their sedentary counterpart6, 7, 8, 9, 11 (Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…A milestone study on elite athletes found that most VA occur in the absence of an underlying heart disease and tend to disappear with detraining, suggesting that they may be considered a feature of the adaptive changes of the athlete's heart 4, 5. However, these findings were limited to a single‐center experience and were not in keeping with the results of old studies performed in the 1980s and 1990s, which demonstrated no differences in the VA burden at 24‐hour ambulatory electrocardiographic monitoring between athletes and sedentary individuals 6, 7, 8, 9, 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, VA's are sensitive to deconditioning in athletes with and without structural heart disease. Biffi et al (2004) reported an 80% decrease in frequency and complexity of ventricular arrhythmias (from 10,611 ± 10,078 to 2,165 ± 4,877), as well as a 90% decrease in the occurrence of nonsustained ventricular tachycardia's with deconditioning. Using longitudinal data, the authors conclude that frequent and complex ventricular tachyarrhythmias are not ominous in trained athletes without cardiovascular abnormalities, and that these rhythm disturbances are another expression of the athlete's heart.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 97%
“…Recent data has documented an increased prevalence of substantial ectopy with frequent premature beats and complex ventricular tachyarrhythmias (including couplets and bursts of non-sustained ventricular tachycardia), predominantly occurring within endurance-trained veteran athletes (Jensen-Urstad et al 1998;Biffi et al 2002Biffi et al , 2004Ector et al 2007;Whyte et al 2007;Whyte 2008;Mont et al 2009). Biffi et al (2008) reported that intensive endurance training may shift cardiovascular autonomic modulation from parasympathetic toward sympathetic dominance, thereby enhancing cardiovascular performance at peak training (Iellamo et al 2002).…”
Section: Supraventricular Complex Ventricular and Profound Bradyarrhmentioning
confidence: 99%
See 1 more Smart Citation